Energy conservation tracking of Thailand's energy and GHG mitigation plan: A case of Thailand's textile industry - Tassawan Jaitiang (2020)
© 2019 Thailand's textile industry is the traditional industrial sector which shows the continuous increase in energy consumption and Energy Intensity (EI) index, primarily on electrical and thermal energy. This paper aims to track the implementation of energy conservation measures through the textile industry to meet Thailand's target of Energy Efficiency Plan 2015- a=2036 (EEP2015), Alternative Energy Development Plan 2015–2036 (AEDP2015) and NDC Road,map by absolute and intensity indicators. As the analyst indicates that energy consumption in this sector will grow while EI can be reduced. 4 Scenarios of energy conservation and the implementation of renewable energy in the sector are studied; (1) BAU, (2) switching to high-efficiency equipment and waste heat recovery, (3) solar PV utilization, and (4) the combination of the equipment switching, heat recovery, and Solar PV utilization. It is deduced that, in 2036, Energy consumption and EI of scenario 2 and 4 is approximately reduced for 16.63% in comparison with BAU which implies the reduction of 373.41 ktoe energy consumption. This is well over the EEP2015 target by 9.94% as solar PV utilization plays small influences. Solar PV systems alone cannot primarily help the textile industry to meet AEDP2015 target. It is recommended that textile industry should implement more renewable-related measures or the alteration of policy and technology is needed. In the case of the environment impacts, GHG emission and GHG mitigation show consistent results with the energy consumption. In 2036, scenario 1 suggests GHG emission of 13,482.58 Gg CO2-eq and GHG Intensity (GHGI) of 29.54 Gg CO2-eq/billion baht. Scenario 2, 3 and 4 possibly reduce GHG emission and GHGI in 2036 as 16.67%, 1.15% and 17.82% above the BAU, respectively. The target of NDC roadmap is to mitigate GHG within 2030. Scenario 4 can mitigate 53.75% over the target while scenario 2 can mitigate more than 41.11%.